2016
DOI: 10.1590/1414-431x20165340
|View full text |Cite
|
Sign up to set email alerts
|

Impact of acute undernutrition on growth, ileal morphology and nutrient transport in a murine model

Abstract: Undernutrition represents a major public health challenge for middle- and low-income countries. This study aimed to evaluate whether a multideficient Northeast Brazil regional basic diet (RBD) induces acute morphological and functional changes in the ileum of mice. Swiss mice (∼25 g) were allocated into two groups: i) control mice were fed a standard diet and II) undernourished mice were fed the RBD. After 7 days, mice were killed and the ileum collected for evaluation of electrophysiological parameters (Ussin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 39 publications
3
15
1
Order By: Relevance
“…Within the past 2 decades, several factors that directly or indirectly influence the PepT1 on either the transcription level or the intracellular trafficking have been investigated. For example, multiple studies revealed that the expression of PepT1 was increased under acute undernutrition on nutrient transport, 51 , 52 similar to results from a previous morphological study of the rat intestinal lining in relation to depletion of body stores during fasting and after refeeding. In this study, Habold et al proposed the major mechanisms of intestinal adaptation to fasting and refeeding and showed a remarkable increase in the apical PepT1 expression during both metabolic fasting phases.…”
Section: Resultssupporting
confidence: 75%
“…Within the past 2 decades, several factors that directly or indirectly influence the PepT1 on either the transcription level or the intracellular trafficking have been investigated. For example, multiple studies revealed that the expression of PepT1 was increased under acute undernutrition on nutrient transport, 51 , 52 similar to results from a previous morphological study of the rat intestinal lining in relation to depletion of body stores during fasting and after refeeding. In this study, Habold et al proposed the major mechanisms of intestinal adaptation to fasting and refeeding and showed a remarkable increase in the apical PepT1 expression during both metabolic fasting phases.…”
Section: Resultssupporting
confidence: 75%
“…Regional Basic Diet (RBD) is an experimental rodent diet mimicking dietary pattern from the northeast Brazilian population, characterized by reduced protein (7%), fat (8.2%), and vitamins and minerals content, triggering clinical symptoms such as reduced weight gain in rats [56,57], which has been confirmed in later studies [32,33,58]. Three weeks of this RBD in weaned mice induced jejunal hyperpermeability [32], which was related to a decreased jejunal expression of the tight junction protein claudin-3 [32].…”
Section: Undernutrition Modelsmentioning
confidence: 99%
“…Three weeks of this RBD in weaned mice induced jejunal hyperpermeability [32], which was related to a decreased jejunal expression of the tight junction protein claudin-3 [32]. In addition, ileal permeability was also increased, despite the increased ileal claudin-2 and occludin mRNA expression [33]. In contrast, after 10 days of RBD in weaned mice, ileal occludin expression was decreased without measurable impact on gut permeability [59] and jejunal villous and crypt atrophy were noted [32].…”
Section: Undernutrition Modelsmentioning
confidence: 99%
“…According to McCracken and Edinger (2013), one of the regulatory pathways of gene expression of the intestinal nutrient transporter is the response to the availability of nutrient; thus nutrient reduction elicits the adaptive up-regulation of transporters for the little nutrients. Studies have revealed that acute undernutrition up-regulates the mRNA expression of PepT1 (Sampaio et al, 2016). Furthermore, a greater amount of PepT1 and EAAT3 mRNA has been associated with the poor dietary protein quality (Osmanyan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%